Properties of the ground state of electronic excitations in carbon-like nanocones - Sitenko, Y.A.; Gorkavenko, V.M. (Физика низких температур, 2018)
On the basis of the continuum model for long-wavelength charge carriers, originating in the tight-binding approximation for the nearest-neighbour interaction of atoms in the crystalline lattice, we consider quantum
ground-state effects of electronic excitations in Dirac materials with two-dimensional monolayer honeycomb
structures warped into nanocones by a disclination; the nonzero size of the disclination is taken into account, and
a boundary condition at the edge of the disclination is chosen to ensure self-adjointness of the Dirac–Weyl Hamiltonian operator. We show that the quantum ground-state effects are independent of the disclination size and
find circumstances when they are independent of a parameter of the boundary condition. The magnetic flux circulating in the angular direction around the nanocone apex and the pseudomagnetic flux directed orthogonally to
the nanocone surface are shown to be induced in the ground state. На основі континуальної моделі для довгохвильових зарядових носіїв, що побудована в наближенні сильного зв'язку
у взаємодії найближчих сусідніх атомів кристалічної гратки,
розглянуто квантові ефекти основного стану електронних
збуджень в діракових матеріалах із двовимірними одношаровими сотовими структурами, скрученими дисклинацією у
наноконуси; враховується ненульовий розмір дисклинації, а
гранична умова на краю дисклинації вибирається такою, що
забезпечує самосполучення гамільтонова оператора Дірака–
Вейля. Показано, що квантові ефекти основного стану не
залежать від розміру дисклинації, та знайдено обставини,
коли вони не залежать від параметра граничної умови. Показано, що в основному стані індукуються магнітний потік,
котрий циркулює в кутовому напрямку навколо вершини
наноконуса, та псевдомагнітний потік, який спрямований
ортогонально до поверхні наноконуса. Исходя из континуальной модели для длинноволновых
зарядовых носителей, построенной в приближении сильной
связи для взаимодействия ближайших соседних атомов в
кристаллической решетке, рассмотрены квантовые эффекты
основного состояния электронных возбуждений в дираковских материалах с двумерными однослойными сотовыми
структурами, скрученными дисклинацией в наноконусы;
учитывается ненулевой размер дисклинации, а граничное
условие на краю дисклинации выбирается так, что обеспечивается самосопряженность гамильтонова оператора Дирака–
Вейля. Показано, что квантовые эффекты основного состояния
не зависят от размера дисклинации, и найдены обстоятельства,
при которых они не зависят от параметра граничного условия.
Показано, что в основном состоянии индуцируются магнитный поток, циркулирующий в угловом направлении вокруг
вершины наноконуса, и псевдомагнитный поток, направленный ортогонально к поверхности наноконуса.